ORGANIZATION OF LEISURE ACTIVITIES IN MATHEMATICS FOR SCHOOLCHILDREN USING THE MEANS OF FILM PEDAGOGY - I.K KONDAUROVA; K.T ZHUBANOVA (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
The article clarifies the definitions of the concepts: "leisure activities of schoolchildren" and "leisure program". Leisure programs are implemented through a variety of leisure activities. The study of mathematics is quite time-consuming compared to other school subjects, and this greatly complicates the organization of mathematical leisure activities, which have recently been increasingly conducted with the use of. means of film pedagogy (movies, cartoons, etc.). The article presents the developed and experimentally tested methodological support of the leisure program in mathematics for schoolchildren "Full-length mathematics". The main idea of the leisure program is that each of its activities is based on a movie (cartoon), in the name of which a number appears. Each event of the leisure program is preceded by a joint viewing of a movie (cartoon) or part of it with a mandatory subsequent discussion. The purpose of the program is to develop cognitive interest in mathematics using the means of film pedagogy. The article contains a fragment of one of the activities of the leisure program-the mathematical quest "Around the World in 80 days". The approbation of the leisure program "Full-length Mathematics" confirmed the developing effect of conducting intellectual and leisure activities using the means of film pedagogy.